Fixation methods for mandibular advancement and their effects on temporomandibular joint: a finite element analysis study - Demircan, Sabit; Uretürk, Erdoğan Utku; Apaydın, Ayşegül; Şen, Sinan (BioMed research international, 2020)
Objectives: Bilateral sagittal split osteotomy (BSSO) is a common surgical procedure to correct dentofacial deformities that involve the mandible. Usually bicortical bone fixation screw or miniplates with monocortical bone fixation screw were used to gain stability after BSSO. On the other hand, the use of resorbable screw materials had been reported. In this study, our aim is to determine first stress distribution values at the temporomandibular joint (TMJ) and second displacement amounts of each mandibular bone segment. Methods. A three-dimensional virtual mesh model of the mandible was constructed. Then, BSSO with 9 mm advancement was simulated using the finite element model (FEM). Fixation between each mandibular segment was also virtually performed using seven different combinations of fixation materials, as follows: miniplate only (M), miniplate and a titanium bicortical bone fixation screw (H), miniplate and a resorbable bicortical bone fixation screw (HR), 3 L-shaped titanium bicortical bone fixation screws (L), 3 L-shaped resorbable bicortical bone fixation screws (LR), 3 inverted L-shaped titanium bicortical bone fixation screws (IL), and 3 inverted L-shaped resorbable bicortical bone fixation screws (ILR). Results. At 9 mm advancement, the biggest stress values at the anterior area TMJ was seen at M fixation and LR fixation at posterior TMJ. The minimum stress values on anterior TMJ were seen at L fixation and M fixation at posterior TMJ. Minimum displacement was seen in IL method. It was followed by L, H, HR, M, ILR, and LR, respectively. Conclusion. According to our results, bicortical screw fixation was associated with more stress on the condyle. In terms of total stress value, especially LR and ILR lead to higher amounts.